Oral Microbiome Metabarcoding in Two Invasive Small Mammals from New Zealand - Arsalan Emami-Khoyi; Isma Benmazouz; Adrian M. Paterson; James G. Ross; Elaine C. Murphy; Jennifer Bothwell; Hossein Alizadeh; Bettine Jansen van Vuuren; Peter R. Teske (Diversity, 2020)
All multicellular organisms host a wide diversity of microorganisms in and on their bodies, which are collectively known as their microbiome. Characterising microbial communities that inhabit different body niches in wild animals is critical to better understand the dynamics of microbiome diversityand its functional significance. The current study is the first to apply massively parallel sequencing of 16S rRNA to characterise the microbial diversity and functional content of oral microbiota in two of New Zealand’s most important invasive mammals, the omnivorous common brushtail possum (Trichosurus vulpecula) and the carnivorous stoat (Mustela erminea). In total, strains of bacteria belonging to 19 different phyla, 27 classes, 52 orders, 103 families, 163 genera and 51 known species were identified from the oral cavities of the study species. Strains of the phyla Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria dominated the core oral microbial diversity in both species, while other taxa were comparatively less abundant. Despite invasive populations typically demonstrating limited genetic variation, intraspecific variation of the core bacterial taxa in the oral microbiota was considerable. This suggests that a complex interaction between genetic, physiological, and environmental factors determines the diversity of the study species’oral microbiome.